Synthesis of 3-((2-hydroxybenzylidene)amino)-6- (hydroxymethyl)tetrahydro-2H-pyran-2,4,5-triol as Carbon Steel Corrosion Inhibitor in HCl 1M - Linata, Alfontius
Corrosio n is a problem that always found on the i nner surface of pi pes t h at used i n various industries. As a result, pipeline leakage can occur and resulting in en v ironmental pollution and material losses. Corrosion prevention on the inner surface of pipes can be done by adding corrosion in h ibi tors. Schiff base deriva ti ve compounds that can be synthesized from compounds with amine and aldehyde groups are used as an effecti v e corrosion inhibitor due to the presence of imine groups. Glucosamine is one of teh compound that provide amines, which is a chitosan monomer that can be isolated from shrimp shell waste. 3-((2- hydroxybenzylidene)amino ) -6- ( hydroxymethyl)tetrahydro-2H -pyran-2 ,4,5-triol which is the result of synthesis between glucosamine and salic y laldeh yde, can be used as an corrosion i nhibitor of carbon steel which i s en v ironmentally friendly. To get g l ucosamine, chitin needs to be isolated from shrimp shells first. The isolation process is carried out by deproteination, demineralization, and decolorizat ion. Chitin reco v ery in this research was 22 ,09%. Chitin then hydrol y zed with concentrated HCl at 90°C. Based on the characterization usin g thin la yer chromato g raphy and infrared spectroscopy (IR), glucosamine successfully isolated from shrimp shells. Yield of glucosamine was 51 ,98%. 3-((2- h ydroxybenzy1 idene)amino)-6-(hydrox y meth yl )tetrahydro -2 H-pyran -2 ,4,5-trio1 was then synthesized from the isolated glucosamine, salicylaldehyde, and KHC03 at 50 °C for 3 hours. The result of synthesis of this compound was 94.13% . Based on the characterizat ion using infrared spectroscopy (IR) and Nuclear Mag netic Resona nce (N M R ), 3 -((2-hydrox ybenzylidene)ami no )-6-(hydroxymethyl)tetrahydro -2H -pyran- 2 ,4,5- triol has been successfully synthesized. The corrosion inhibition power of these compounds was then measured through the Electrochemical Impedance Spectroscopy (EIS) measurement method at concentrations of 25 ppm , 50 ppm, 75 ppm , I 00 ppm, and 1 2 5 ppm at room temperature, 35 °C, 45 °C and 55 oc_ AC potential is used with an amplitude of 10 mY and a frequency range from 10kHz to 100 mHz. Optimal results are obtained at 45°C with an efficiency of 62.41 %. Poten tiodynamic po l ar ization measurements were carried out at concentrations of 25 ppm , 50 ppm , 75 ppm , 100 ppm , and 125 ppm, at a temperature of 45 °C in a 1 M HCl en v ironment using carbon steel working el ectrodes. Optimal resu l ts were obtained at a concentrat ion of I 00 ppm with an efficiency of 77.51 %. Based on the corrosion potential produced , the 3-((2- hydroxybenzyl idene)amino )-6-( hydroxymethyl )tetrahydro-2H-pyran-2 ,4,5-trio I compound is a m i xed inhib i tor.